Red cell distribution width as a predictor for bronchopulmonary dysplasia in premature infants - Hayato Go (Nature Portfolio, 2021)
Abstract Bronchopulmonary dysplasia (BPD) is the most common morbidity complicating preterm birth. Red blood cell distribution width (RDW), a measure of the variation red blood cell size, could reflect oxidative stress and chronic inflammation in many diseases such as cardiovascular, pulmonary, and other diseases. The objectives of the present study were to evaluate perinatal factors affecting RDW and to validate whether RDW could be a potential biomarker for BPD. A total of 176 preterm infants born at < 30 weeks were included in this study. They were categorized into BPD (n = 85) and non-BPD (n = 91) infants. RDW at birth and 14 days and 28 days of life (DOL 14, DOL 28) were measured. Clinical data were obtained from all subjects at Fukushima Medical University (Fukushima, Japan). The mean RDW at birth, DOL 14 and DOL 28 were 16.1%, 18.6%, 20.1%, respectively. Small for gestational age (SGA), chorioamnionitis (CAM), hypertensive disorders of pregnancy (HDP), gestational age and birth weight were significantly associated with RDW at birth. SGA, BPD and red blood cell (RBC) transfusion before DOL 14 were associated with RDW at DOL 14. BPD and RBC transfusion before DOL 14 were associated with RDW at DOL 28. Compared with non-BPD infants, mean RDW at birth DOL 14 (21.1% vs. 17.6%, P < 0.001) and DOL 28 (22.2% vs. 18.2%, P < 0.001) were significantly higher in BPD infants. Multivariate analysis revealed that RDW at DOL 28 was significantly higher in BPD infants (P = 0.001, odds ratio 1.63; 95% CI 1.22–2.19). Receiver operating characteristic analysis for RDW at DOL 28 in infants with and without BPD yielded an area under the curve of 0.87 (95% CI 0.78–0.91, P < 0.001). RDW at DOL 28 with mild BPD (18.3% vs. 21.2%, P < 0.001), moderate BPD (18.3% vs. 21.2%, P < 0.001), and severe BPD (18.3% vs. 23.9%, P < 0.001) were significantly higher than those with non-BPD, respectively. Furthermore, there are significant differences of RDW at DOL 28 between mild, moderate, and severe BPD. In summary, we conclude that RDW at DOL 28 could serve as a biomarker for predicting BPD and its severity. The mechanism by which RDW at DOL 28 is associated with the pathogenesis of BPD needs further elucidation.